Retraction Note: The oncogenic Golgi phosphoprotein 3 like overexpression is associated with cisplatin resistance in ovarian carcinoma and activating the NF-κB signaling pathway - Shanyang He; Gang Niu; Jianhong Shang; Yalan Deng; Zhiyong Wan; Cai Zhang; Zeshan You; Hongwei Shen (Journal of Experimental & Clinical Cancer Research)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s13046-017-0607-0.